2006
DOI: 10.1038/oby.2006.236
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting Energy Expenditure after 40 Minutes of Aerobic But Not Resistance Exercise

Abstract: HUNTER, GARY R., NUALA M. BYRNE, BARBARA A. GOWER, BOVORN SIRIKUL, AND ANDREW P. HILLS. Increased resting energy expenditure after 40 minutes of aerobic but not resistance exercise. Obesity. 2006;14:2018 -2025. Objective: Resting energy expenditure (REE) is increased 24 hours after high-intensity aerobic exercise lasting 60 minutes, whereas results have been inconsistent after resistance training and aerobic exercise of shorter duration. The objective of the study was to compare the effects of 40 minutes of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
1
31
0
7
Order By: Relevance
“…Previous work has shown that aerobic and resistance training results in increased REE (18; 37) and TEE (10; 18) supporting the hypothesis that exercise training, especially resistance training, increases TEE by increasing REE, probably through either increased fat free mass (15) or post-exercise elevation of metabolism that lasts more than 24 hours (12; 38). In addition, exercise training increases locomotion economy and ease (4; 7; 16; 19; 28; 34; 35) and AEE (10) and NEAT (10) while others show reductions (6; 10).…”
Section: Discussionmentioning
confidence: 62%
“…Previous work has shown that aerobic and resistance training results in increased REE (18; 37) and TEE (10; 18) supporting the hypothesis that exercise training, especially resistance training, increases TEE by increasing REE, probably through either increased fat free mass (15) or post-exercise elevation of metabolism that lasts more than 24 hours (12; 38). In addition, exercise training increases locomotion economy and ease (4; 7; 16; 19; 28; 34; 35) and AEE (10) and NEAT (10) while others show reductions (6; 10).…”
Section: Discussionmentioning
confidence: 62%
“…The increased energy intake balanced against energy expenditure (energy flux) has been shown in several studies to contribute to the elevated 24-h energy expenditure on exercise days or in trained individuals (5,8,12). Other potential factors include homeostatic disturbance from vigorous exercise, as theorized by Bahr et al (4), increased circulation of stress hormones and sympathetic tone (14), and recovery from decreased muscle glycogen levels (14).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be partly explained by the lack of difference in hunger control observed between adolescents following either high-or low-protein diets (49,50) . Similarly, the lack of evidence supporting the efficacy of resistance training in the treatment of adolescent obesity (13,16) may be explained by the greater caloric expenditure required for the performance of aerobic as opposed to resistance training (51) . In accordance, the former is generally associated with slightly greater improvements in body weight and composition in obese adolescents, despite greater gains in skeletal muscle following resistance training (31,52,53) , perhaps due to a resultant reduction in REE-to-FFM.…”
Section: Efficacy Of High-protein Diets and Resistance Training In Obmentioning
confidence: 99%